A Feasibility study on GM-1 9600 Baud Radio Modem - Castro, Carlo Alfred S. (College of Engineering, 1996)
The name of the Enterprise would be CLS Enterprises Inc. This name was coined from the initials of the project proponent?s surnames. It is also a good name because it is attuned to the technical industries in the Market today. The location of the plant and head office would be located at #617 Bonifacio Avenue, Mandaluyong City. The modem is an inexpensive but portable alternative to the modems existing in the market today. This type of modem does not require the use of telephone lines for operation. While the inventor, Rajah Castillo, initially designed the product to connect two LAN (Local Area Network) based computers (i.e. LAN in UP connected to LAN in Ateneo), the proponents of this study have considered other potential users. For example the mobile laptop computer users are, for one, may benefit a lot from this product. The men behind the product are under the DOST-ASTI Engineering and Communications Division. The Project?s long range objectives are: *To establish a stable market share in the present economy, *To generate a sustainable income from operations, *To curve the unemployment rate which is prevalent in the country today and *To contribute to the increase of the gross national product (GNP). Feasibility Criteria- a) That there is an adequate demand to be able to sustain a cost of operation and generate an attractive rate of return for its investors and service debt to its creditors. B)There should also be a net positive gain or benefit to the economy. Market Feasibility: The group was able to prove that the production of the said GM-19.6 Baud Radio Modem would have its own share in the increase of demand for information dissemination together with the growing demand for access to the Information Superhighway. Since the product's service is unique and the first in the country, it has no competitors and its market share is 100%. The project has a total aggregate demand of 2,162 units in its first year. There is just a need to further improve on the project and promote this project to the consumers in order of the latter to get to know about the benefits of the said product. Technical Feasibility: The size, location, technology and timing of the project are proportionate and appropriate to the demand. All the technical features are reasonably well-defined and are found to be workable, accurate and acceptable. The input resources such as labor, raw materials, equipment are available in the required quality and quantity with a reasonable cost. The total project cost is P10,128,115. Financial Feasibility: From the Income Statements, Statement of Cash flows and the Financial Ratios, it can be concluded that the project is financially feasible. Other reasons are as follows: *It generates sufficient income of P 2,489,108 for the first year, *It has a Net Present Value equal to P 5,693,371.82, *It has an IRR of approximately 218%.